Synthesis and in vitro antiproliferative activity of C5-benzyl substituted 2-amino-pyrrolo[2, 3-d]pyrimidines as potent Hsp90 inhibitors. Issue 2 (15th January 2017) - Lee, Ju-Hyeon; Shin, Sang Chul; Seo, Seon Hee; Seo, Young Ho; Jeong, Nakcheol; Kim, Chan-Wha; Kim, Eunice EunKyeong; Keum, Gyochang
Graphical abstract: Abstract: A novel series of heat shock protein 90 (Hsp90) inhibitors was identified by X-ray crystal analysis of complex structures at solvent-exposed exit pocket C. The 2-amino-pyrrolo[2, 3- d ]pyrimidine derivatives, 7-deazapurines substituted with a benzyl moiety at C5, showed potent Hsp90 inhibition and broad-spectrum antiproliferative activity against NCI-60 cancer cell lines. The most potent compound, 6a, inhibited Hsp90 with an IC50 of 36 nM and showed a submicromolar mean GI50 value against NCI-60 cell lines. The interaction of6a at the ATP-binding pocket of Hsp90 was confirmed by X-ray crystallography and Western blot analysis.